3D Bi2MoO6 Nanosheet/TiO2 Nanobelt Heterostructure: Enhanced Photocatalytic Activities and Photoelectochemistry Performance - Tian, Jian; Hao, Pin; Wei, Na; Cui, Hongzhi; Liu, Hong (ACS catalysis, 2015)
We employed TiO2 nanobelts as the synthetic template and developed three-dimensional (3D) porous Bi2MoO6 nanosheet/TiO2 nanobelt heterostructures with a few-layer and uniform Bi2MoO6 nanosheets by a simple hydrothermal method. The as-prepared Bi2MoO6 nanosheet/TiO2 nanobelt heterostructure shows an excellent photodegradation performance under UV and visible light irradiation. Importantly, such a heterostructure possesses high photocatalytic oxygen production with a rate of 0.668 mmol h–1 g–1. Moreover, the Bi2MoO6 nanosheet/TiO2 nanobelt heterostructure shows an enhanced photoelectochemistry performance under irradiation of solar illumination. The current research can offer an alternative route for designing a 3D heterostructure system to effectively utilize broad-spectrum solar light.